Benefit–Risk Summary of Nivolumab for the Treatment of Patients with Unresectable Advanced, Recurrent, or Metastatic Esophageal Squamous Cell Carcinoma After Prior Fluoropyrimidine‐ and Platinum‐Based Chemotherapy. (11th January 2021) - Pelosof, Lorraine; Saung, May Tun; Donoghue, Martha; Casak, Sandra; Mushti, Sirisha; Cheng, Joyce; Jiang, Xiling; Liu, Jiang; Zhao, Hong; Khazraee, Maryam; Goldberg, Kirsten B.; Theoret, Marc; et al.
Abstract: : On June 10, 2020, the U.S. Food and Drug Administration (FDA) approved nivolumab (OPDIVO; Bristol Myers Squibb, New York, NY) for the treatment of patients with unresectable advanced, recurrent, or metastatic esophageal squamous cell carcinoma (ESCC) after prior fluoropyrimidine‐ and platinum‐based chemotherapy. Approval was based on the results of a single, randomized, active‐control study (ATTRACTION‐3) that randomized patients to receive nivolumab or investigator's choice of taxane chemotherapy (docetaxel or paclitaxel). The study demonstrated a significant improvement in overall survival (OS; hazard ratio = 0.77; 95% confidence interval: 0.62–0.96; p = .0189) with an estimated median OS of 10.9 months in the nivolumab arm compared with 8.4 months in the chemotherapy arm. Overall, fewer patients in the nivolumab arm experienced treatment‐emergent adverse events (TEAEs) of any grade, grade 3–4 TEAEs, and serious adverse events compared with the control arm. The safety profile of nivolumab in patients with ESCC was generally similar to the known safety profile of nivolumab in other cancer types with the following exception: esophageal fistula was identified as a new, clinically significant risk in patients with ESCC treated with nivolumab. Additionally, the incidence of pneumonitis was higher in the ESCC population than in patients with other cancer types who are treated with nivolumab. This article summarizes the FDA review of the data supporting the approval of nivolumab for the treatment of ESCC. Implications for Practice: The approval of nivolumab for the treatment of adult patients with unresectable advanced, recurrent, or metastatic esophageal squamous cell carcinoma (ESCC) after prior fluoropyrimidine‐ and platinum‐based chemotherapy was based on an overall survival (OS) benefit from a randomized, open‐label, active‐controlled study called ATTRACTION‐3. Prior to this study, no drug or combination regimen had demonstrated an OS benefit in a randomized study for patients with ESCC after prior fluoropyrimidine‐ and platinum‐based chemotherapy. Abstract : This article summarizes the FDA review of the data supporting the approval of nivolumab for the treatment of recurrent or metastatic esophageal squamous cell carcinoma.